Cofilin, a hypoxia‐regulated protein in murine lungs identified by 2DE: Role of the cytoskeletal protein cofilin in pulmonary hypertension. Issue 1 (11th January 2013) - Veith, Christine; Schmitt, Sigrid; Veit, Florian; Dahal, Bhola Kumar; Wilhelm, Jochen; Klepetko, Walter; Marta, Gabriel; Seeger, Werner; Schermuly, Ralph Theo; Grimminger, Friedrich; Ghofrani, Hossein A.; Fink, Ludger; et al.
<x xml:space="preserve">Abstract</x> Chronic alveolar hypoxia induces vascular remodeling processes in the lung resulting in pulmonary hypertension (PH). However, the mechanisms underlying pulmonary remodeling processes are not fully resolved yet. To investigate functional changes occurring during hypoxia exposure we applied 2DE to compare protein expression in lungs from mice subjected to 3 h of alveolar hypoxia and those kept under normoxic conditions. Already after this short‐time period several proteins were significantly regulated. Subsequent analysis by MALDI‐MS identified cofilin as one of the most prominently upregulated proteins. The regulation was confirmed by western blotting and its cellular localization was determined by immunohisto‐ and immunocytochemistry. Interestingly, enhanced cofilin serine 3 phosphorylation was observed after short‐term and after chronic hypoxia‐induced PH in mice, in pulmonary arterial smooth muscle cells (PASMC) from monocrotaline‐induced PH in rats, in lungs of idiopathic pulmonary arterial hypertension patients and in hypoxic or platelet‐derived growth factor BB‐treated human PASMC. Furthermore, elevated cofilin phosphorylation was attenuated by curative treatment of monocrotaline‐induced PH in rats and hypoxia‐induced PH in mice with the PDGF‐BB receptor antagonist imatinib. In conclusion, short‐term hypoxic exposure induced prominent changes in lung protein regulation. These very early changes allowed us to identify potential triggers of PH. Thus, respective 2DE analysis can lead to the identification of new target proteins for the possible treatment of PH.